Current perspectives in assessing humoral immunity after measles vaccination. (2nd January 2019) - Haralambieva, Iana H.; Kennedy, Richard B.; Ovsyannikova, Inna G.; Schaid, Daniel J.; Poland, Gregory A.
ABSTRACT: Introduction : Repeated measles outbreaks in countries with relatively high vaccine coverage are mainly due to failure to vaccinate and importation; however, cases in immunized individuals exist raising questions about suboptimal measles vaccine-induced humoral immunity and/or waning immunity in a low measles-exposure environment. Areas covered : The plaque reduction neutralization measurement of functional measles-specific antibodies correlates with protection is the gold standard in measles serology, but it does not assess cellular-immune or other parameters that may be associated with durable and/or protective immunity after vaccination. Additional correlates of protection and long-term immunity and new determinants/signatures of vaccine responsiveness such as specific CD46 and IFI44L genetic variants associated with neutralizing antibody titers after measles vaccination are under investigation. Current and future systems biology studies, coupled with new technology/assays and analytical approaches, will lead to an increasingly sophisticated understanding of measles vaccine-induced humoral immunity and will identify 'signatures' of protective and durable immune responses. Expert opinion : This will translate into the development of highly predictive assays of measles vaccine efficacy, effectiveness, and durability for prospective identification of potential low/non-responders and susceptible individuals who require additional vaccine doses. Such new advances may drive insights into the development of new/improved vaccine formulations and delivery systems.